Analysis of Tiktok Trends on The Development of Social Behavior in Early Children - Osriyenti; Rakimahwati (Bisma The Journal of Counseling, 2022)
This research is motivated by factual conditions that occur in society, especially in early childhood, the widespread use of gaway in all circles of society. The purpose of this study was to see the trend tiktok on the development of early childhood social behavior. The research method uses a literature study approach. The data collection technique is by collecting several previous studies to answer the feasibility, responses, and findings after seeing the condition of the development of early childhood social behavior. The previous research that has been collected is then compiled, analyzed, and concluded so as to get a conclusion regarding the analysis of the trend of shaking tiktok on the development of early childhood social behavior. The conclusion in this study can be drawn that from the results of data analysis it was found that tiktok can change children's behavior, tiktok affects children's concentration in learning, makes children negligent in learning, tiktok makes children dishonest, tiktok makes children disrespect their parents, children spends a lot of time playing tiktok. Therefore, parental supervision is needed so that children can avoid the bad effects of using tiktok.